2008
DOI: 10.1111/j.1582-4934.2008.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Neovascularization in an arterio‐venous loop‐containing tissue engineering chamber: role of NADPH oxidase

Abstract: Using an in vivo arterio-venous loop-containing tissue-engineering chamber, we have created a variety of vascularized tissue blocks, including functional myocardium. The viability of the transplanted cells is limited by the rate of neovascularization in the chamber. A Nox2-containing nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is thought to have a critical role in ischaemic angiogenesis. In this study we investigated whether NADPH oxidase is involved in the neovascularization process in the tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 38 publications
(57 reference statements)
3
32
0
Order By: Relevance
“…This is not the first instance we have reported a role for Nox2 in vascular sprouting. Using a chamber model of arterial venous loop re-construction, we have shown a high level of Nox2 expressed in endothelial cells of newly developed blood vessels sprouting from the loop and local administration of Nox inhibitors apocynin or gp91ds-tat peptide to the chamber suppressed angiogenesis [11]. It will be important to focus future studies on investigating the effects of long term treatments with specific Nox2 inhibitors or Nox2 deficient mice on angiogenesis after stroke to confirm the current findings.…”
Section: Resultssupporting
confidence: 58%
“…This is not the first instance we have reported a role for Nox2 in vascular sprouting. Using a chamber model of arterial venous loop re-construction, we have shown a high level of Nox2 expressed in endothelial cells of newly developed blood vessels sprouting from the loop and local administration of Nox inhibitors apocynin or gp91ds-tat peptide to the chamber suppressed angiogenesis [11]. It will be important to focus future studies on investigating the effects of long term treatments with specific Nox2 inhibitors or Nox2 deficient mice on angiogenesis after stroke to confirm the current findings.…”
Section: Resultssupporting
confidence: 58%
“…The NADPH oxidase family of ROS-generating enzymes is the key source of ROS in the vascular system and these enzyme complexes are crucial players in both physiological and pathological angiogenesis [32,33]. We have previously demonstrated that NADPH oxidase facilitates angiogenic responses in wound healing in a variety of tissues in vivo [34,35]. Studies of the roles of different isoforms of NADPH oxidase with genetically modified animals and in vivo siRNA approaches have also highlighted the involvement of Nox in VEGF-dependent neovascularization of hypoxic retinas in animals with oxygen-induced retinopathy [16,28,36].…”
Section: Discussionmentioning
confidence: 98%
“…Chemical cautery-induced fibrovascular proliferation is reduced in Nox2-deficient mice as is indicated by lower burn severity scores at day 7, as well as reduced corneal neovascularization at days 7 and 14. Although it might be possible that the reductions in corneal neovascularization and Vegf-A observed in Nox2 KO mice were consequences of the less severe corneal cautery in these than in wild type mice, this is unlikely for several reasons: (1) corneal cautery was performed in accordance with a standardized protocol by a single experienced operator masked to the genotype of each mouse; (2) increased Nox2 expression and the generation of ROS are associated with the inflammatory response after tissue injury and regeneration [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a Nox2-containing nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is known to play a major role in hypoxia-driven angiogenesis. Recently, it could be confirmed that it is involved in the process of neoangiogenesis within the AV loop chamber and that specific inhibitors such as apocynin or gp91ds-tat peptide lead to an inhibition of further vessel growth [25]. …”
Section: The Arteriovenous Loop Model: Methods and Mechanism Behind Thmentioning
confidence: 99%